Efficiency of Use of "Logistics" Projects in Surkhandarya Region and Prospects of Ensuring Economic Growth of the Region - Saydalimov Abdukarim Karamatovich; Saydaliev Utkir Shodievich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
in this article, the information on the foreign experience in the formation and development of logistics in the agricultural economy is presented in an in-depth analysis and processing. The article also describes the data of the logistics efficiency evaluation index.